The Preservations of Ambivalent Attachment in Tatyana Tolstaya’s Unnecessary Things - Fransisca Irnidianis Magdalena Suyaji; Dyah Ayu Ratna Jelita; Gunawan Tjokro; Fransiska Litwin Nurni; Ananda Syahromi Putra; Rommel Utungga Pasopati (Gudang Jurnal Multidisiplin Ilmu, 2024)
Abstract This research explores crucial issues regarding processing systems, marketing strategies, and barriers to coconut sugar and rubber production at PTPN 1 Regional 5 Kebun Kalikempit. The aim of the research is to analyze the efficiency of the processing system, evaluate the marketing strategy implemented, and identify the production obstacles faced. Research methods involve field surveys, production data analysis, and interviews with relevant stakeholders. The results of this research reveal the potential for increased efficiency in processing systems, the need to adapt marketing strategies according to market changes, and production constraints that require sustainable solutions to increase productivity in this sector. This study provides in-depth insights that can be the basis for operational and policy improvements at PTPN 1 Regional 5.